Consumer Taxes on Alcohol: An International Comparison over Time. (February 2020) - Anderson, Kym
Abstract: Rates of alcohol taxation, and the types of tax instruments used, vary enormously between countries and have tended to rise in recent times. Within each country, they also vary between beverages and often between qualities and styles of each beverage. This article computes consumer tax equivalents in U.S. dollars per litre of alcohol and as percentages of wholesale prices of representative beverages for 42 high- and middle-income countries. That allows comparisons across countries of taxes not just for each product on its own, but also relative to those for other alcoholic beverages. The wide dispersion of rates and differences in tax instruments across countries and products suggest differing strengths of health and welfare lobbyists and industry groups in influencing government decision-making. (JEL Classifications: D12, D62, E62, H23, I18, P46)